2013
DOI: 10.1111/resp.12122
|View full text |Cite
|
Sign up to set email alerts
|

Effects of whole body vibration training in patients with severe chronic obstructive pulmonary disease

Abstract: WBVT provided significant improvements in functional capacity in severe COPD patients without changes in muscular force.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
99
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(110 citation statements)
references
References 36 publications
8
99
0
3
Order By: Relevance
“…Specifically, we observed a strong effect on 6MWD, which increased by 95.55 ± 76.29 m. The magnitude of the 6WMD improvement was comparable to that described by Pleguezuelos et al (81.2 m) in the stable phase of the disease [27]. Interestingly, 19/20 patients in WBV group (compared to 9/19 in the control group) improved 6MWD by more than 35 m, which is considered as a minimal clinical important difference (MCID) [30].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Specifically, we observed a strong effect on 6MWD, which increased by 95.55 ± 76.29 m. The magnitude of the 6WMD improvement was comparable to that described by Pleguezuelos et al (81.2 m) in the stable phase of the disease [27]. Interestingly, 19/20 patients in WBV group (compared to 9/19 in the control group) improved 6MWD by more than 35 m, which is considered as a minimal clinical important difference (MCID) [30].…”
Section: Discussionsupporting
confidence: 72%
“…To date, trials regarding efficacy of WBV in patients with COPD are scarce. Results from two studies investigating the effects of WBV therapy in patients with stable COPD showed a significantly greater improvement in the 6MWT, and a significant decrease in maximum oxygen desaturation during the 6-MWT than compared to patients in control group [6,27].…”
Section: Discussionmentioning
confidence: 99%
“…Four studies were performed as randomized controlled trials using an adequate quality of methodology. 15,17,19,20 Two studies performed by the same work group used a nonrandomized study design with crossover to sham 16,19 that yielded lower methodological quality ratings.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…It is an efficacious mode of exercise training in patients with COPD that improves exercise capacity and lower limbs functional performance (23)(24)(25). WBVT is also associated with increased irisin levels as marker of muscle activity in COPD and may improve health-related QoL (26).…”
Section: Whole Body Vibration Training (Wbvt) In Long-term (>1 Year) mentioning
confidence: 99%